Quality of care assessment and improvement in aortic stenosis - rationale and design of a multicentre registry (IMPULSE). Issue 1 (December 2017) - Frey, Norbert; Steeds, Richard; Serra, Antonio; Schulz, Eberhard; Baldus, Stephan; Lutz, Matthias; Pohlmann, Christiane; Kurucova, Jana; Bramlage, Peter; Messika-Zeitoun, David
Abstract Background Severe aortic stenosis (AS) is a common, serious valve disease in which no effective medical therapy is available and, if not treated by intervention, has a 5-year survival of only 40–60%. Despite the availability of guidelines supporting the effective use of surgical aortic valve replacement (SAVR) or transcatheter aortic valve implantation (TAVI) to treat the majority of these patients, adherence to these guidelines in clinical practice is still unsatisfactory. Several recent studies have emphasised the necessity for improved communication between multidisciplinary teams, with the aim to ensure that severe AS patients receive appropriate treatment. Methods/design IMPULSE is a prospective, multicentre, European registry designed to gather data over 12 months on the treatment decisions made by referring physicians for patients newly diagnosed with severe AS. Each patient has a follow-up of 3 months. The study will consist of two observational phases to assess the appropriateness and rate of referral based on current guidelines prior to and after an interventional phase aiming to determine whether a simple quality of care intervention improves patient management. Discussion Data will be analysed firstly, to determine the appropriateness of treatment decisions for the management of severe AS in current European clinical practice, and secondly, to evaluate the effectiveness of facilitated data relay from a designated echocardiography department nurse to the referring physician early after diagnosis in improving quality of care. Additionally, variables will be identified that are associated with inappropriate decision-making. Collectively, the aim will be to design a clinical pathway that will improve the timely management of patients with newly diagnosed severe AS.